Navigating Influencer Liability on Social Media: Balancing Profits and Legal Risks - Kassi, Yuliance; Sakmaf, Marius Suprianto; Suryana, Atang (Yayasan Sinergi Kawula Muda, 2024)
This study aims to investigate the legal responsibilities of influencers in social media, focusing on the role of the Indonesian Electronic Information and Transaction Law (UU ITE) in regulating online activities. This research uses qualitative research methods with a case study approach.The study explores how influencers can navigate their legal responsibilities in social media, ensuring that the information they share is accurate and non-misleading. The findings highlight the importance of understanding the legal framework governing online activities, including the UU ITE, and the need for influencers to be aware of their legal obligations. The study contributes to the development of more effective legal frameworks for regulating online activities and ensuring that social media platforms are used responsibly. The results suggest that influencers must be educated about their legal responsibilities and must ensure that the information they share is accurate and non-misleading. The study recommends that influencers develop clear policies and guidelines for their online activities and that they collaborate with brands that share similar values.